Exploring the Practice of the Integrative Approach in Arabic Language Learning at the Madrasah Aliyah Level: Teacher and Student Perspectives - Salma Khaerunnisa; Bilqis Nailatuzzahra; Sania Naftali Zakiah (Gunung Djati Conference Series, 2026)
This study aims to examine how the integrative approach is implemented in Arabic language learning at the Madrasah Aliyah level and to explore teachers’ and students’ perceptions of its effectiveness. In addition, the study seeks to identify the supporting and inhibiting factors in its implementation and to analyze the extent to which the integrative approach can enhance students’ overall language skills. This research employs a descriptive qualitative method, with primary data obtained from interviews and observations, and secondary data sourced from instructional documents. Data collection techniques include in-depth interviews, direct classroom observations, and documentation analysis. Data were analyzed through data reduction, data display, and inductive conclusion drawing to produce a comprehensive understanding of the implementation of the integrative approach in the field. The findings indicate that the application of the integrative approach has had a positive impact on increasing students’ motivation and language proficiency, although its implementation is not yet consistent across all classes. Both teachers and students express positive perceptions; however, limited time, insufficient facilities, and differences in students’ abilities remain major challenges. Overall, the integrative approach holds significant potential to strengthen Arabic language learning, provided it is supported by adequate planning and resources.